Sustainable Development of EU countries: Assessment Methodology and Indicators - Khanova Yelena V.; Skibina Svitlana O. (Problemi Ekonomiki, 2017)
The aim of the article is to substantiate the methodology and indicators for assessment of sustainable development in EU countries at the present stage. The article suggests the use of certain indicators for assessment of sustainable development of EU countries: for economic evaluation – Index of Competitiveness and Index of Economic Freedom; for social evaluation — Life Quality Index, Human Development Index, Index of Knowledge Societies; for environmental evaluation — Environmental Sustainability Index and Environmental Efficiency Index. Each of the selected indexes in EU countries is analyzed. The methodology for calculating the ratio of the economic, social and environmental components of sustainable development for EU countries is presented. Emphasis is placed on the significant regional diversification of sustainable development and its components across EU countries, there identified countries of the strong, medium and weak sustainability.